Effect of Microwave Pretreatment on Grindability of Lead-Zinc Ore - Qing Yu; Dexin Ding; Wenguang Chen; Nan Hu; Lingling Wu; Qiucai Zhang; Yulong Liu; Zhijun Zhang; Feng Li; Xilong Xue; Zhaopeng Li; Guicheng He (Geofluids)
The influence of microwave pretreatment on grindability of lead-zinc ore was studied through comparison analysis on the changes of particle size distribution, percentage of below 0.074 mm, energy consumption, and other indexes of grinding products before and after microwave pretreatment in the ball milling process. The results showed that the grindability of lead-zinc ore was improved obviously by microwave pretreatment. The particle size distribution curve of the grinding products was obviously higher than that of the samples without microwave irradiation. The yield of size fraction below 0.074 mm was also improved in a certain degree. Pulsed microwave irradiation was more effective than continuous microwave irradiation when other microwave parameters were consistent. The comprehensive energy consumption of lead-zinc ore pretreated by different microwave parameters was lower than that without microwave irradiation under the same grinding fineness. The total energy consumption was down by 30.1% when irradiated for 15 s at 7 kW power, and it was lower than that without microwave irradiated. The results showed that pulsed microwave pretreatment was more effective in reducing the comprehensive energy consumption of grinding process for lead-zinc ore. And water quenching after microwave irradiation can improve the grindability and reduce the energy consumption of grinding for lead-zinc ore.